2017
DOI: 10.5194/isprs-archives-xlii-2-w3-39-2017
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Geometric Survey and Structural Modelling of the Dome of Pisa Cathedral

Abstract: ABSTRACT:This paper aims to illustrate the preliminary results of a research project on the dome of Pisa Cathedral (Italy). The final objective of the present research is to achieve a deep understanding of the structural behaviour of the dome, through a detailed knowledge of its geometry and constituent materials, and by taking into account historical and architectural aspects as well. A reliable survey of the dome is the essential starting point for any further investigation and adequate structural modelling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Currently, 3D architectural surveys mainly rely on two modeling methodologies-range-based and image-based [14]. The former exploits TLS to provide 3D point cloud models made of millions of points framed in a common reference system, which can represent the survey object geometry with subcentimeter accuracy [15].…”
Section: Surveyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 3D architectural surveys mainly rely on two modeling methodologies-range-based and image-based [14]. The former exploits TLS to provide 3D point cloud models made of millions of points framed in a common reference system, which can represent the survey object geometry with subcentimeter accuracy [15].…”
Section: Surveyingmentioning
confidence: 99%
“…Therefore, the oval is not exactly inscribed; instead, its layout is obtained through a tangency relationship solely affecting points E, F, G, and H (belonging to the oblique sides of the irregular octagon). The tangency in E, F, G, and H is accurately achieved, taking into account the constructive difficulties and irregularities due to deformations induced by phenomena of deterioration and subsidence of the foundation and elevated structures occurring over nine centuries of life of the building [14].…”
Section: Design Analysis and Constructive Issuesmentioning
confidence: 99%
“…It should be observed that, to the purposes of the present paper, a detailed survey has been necessary because of the absence of dome surveys characterized by high-density and precision. Without being exhaustive, the status quo on the surveys of the Cathedral dome, from the most ancient ones up today is briefly reviewed in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the scientific community tends to utilize both surveys, especially in cultural heritage documentation where the building materials play a pivotal role in the documentation process. In this case, both survey methods are elaborated and integrated, providing a textured 3D model [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%